A-site double rare earth ion co-doped antiferroelectric ceramic and its preparation method and application
By adopting A-position double rare earth ion co-doping and advanced sintering technology in antiferroelectric ceramics, the existing ceramics have low energy storage density, low efficiency and insufficient breakdown electric field resistance, and a ceramic material with high energy storage density and high efficiency are achieved.
Patent Information
- Application Number
- CN202411734178.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing antiferroelectric energy storage ceramic materials have low energy storage density, low energy storage efficiency, and low breakdown electric field resistance.
The structural general formula Pb (1.01-1.5n-y)MnCay (Zr1-xSnx) 0.995O3 of A-position double rare earth ion co-doped antiferroelectric ceramic was used, and the powder was prepared by ball milling and multi-step prefiring. The integrated sintering method of casting molding and extrusion pile burial was prepared to produce ceramics with good density.
The energy storage density of ceramics has been significantly improved to 23~35 J/cm3, the energy storage efficiency has reached 70~92%, and the breakdown electric field has been improved to 800~1240 kV/cm, and the performance is close to that of multi-layer ceramic capacitors.
Smart Images

Figure CN119219415B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage dielectric materials, and more specifically to an A-site double rare earth ion co-doped antiferroelectric ceramic and a preparation method and application thereof. Background Art
[0002] At present, the commonly used energy storage dielectric materials are organic materials, which have low energy storage density and relatively poor temperature stability. In comparison, inorganic dielectric ceramics have better charge and discharge performance and thermal stability. The materials used for energy storage include linear materials, ferroelectric materials and antiferroelectric materials. The polarization intensity of linear materials is low, which restricts their energy storage performance, while the energy loss of ferroelectric materials is large, resulting in low releasable energy storage density. Among them, antiferroelectrics are an important type of functional materials, which are widely used in energy storage capacitors, transducers and voltage modulation elements. The adjacent unit cells that make up this type of material are arranged in reverse parallel within a certain temperature range, and the macroscopic polarization intensity is zero. With the continuous development of microscopic characterization methods and the great potential of antiferroelectric materials in power and electronic equipment, people have carried out more in-depth research on antiferroelectrics. So far, researchers have discovered and reported a variety of antiferroelectric materials, but they are still far behind the research on ferroelectric materials, among which antiferroelectric materials with potential application value are even more scarce. The energy storage density (<15 J / cm 3 ) and low energy storage efficiency and low breakdown electric field resistance.
[0003] Chinese invention patent CN107459350B discloses a dielectric energy storage antiferroelectric ceramic material and its preparation method: mixing an antiferroelectric ceramic material with a negative temperature coefficient of energy storage density and an antiferroelectric ceramic material with a positive temperature coefficient of energy storage density in a mass ratio of (30-80): (20-70) to obtain a mixed powder; adding a polyvinyl alcohol solution to the mixed powder, and then sintering to obtain a dielectric energy storage antiferroelectric ceramic material. The obtained energy storage density stability is greater than 85% in a wide temperature range (20℃-150℃), the energy storage efficiency is 85% (150℃) and the minimum energy storage density is 2.77J / cm 3 energy storage material, but the energy storage density of this invention still needs to be improved. Summary of the invention
[0004] The first aspect of the present invention provides an A-site double rare earth ion co-doped antiferroelectric ceramic, the general structure of which is: Pb (1.01-1.5n-y) M n Ca y (Zr 1-x Sn x ) 0.995O3; where M includes rare earth elements, and 0 < x ≤ 0.5, 0 < n ≤ 0.05, 0 < y ≤ 0.05; the ceramic has an energy storage density of 23 - 35 J / cm 3 , and an energy storage efficiency of 70 - 92%.
[0005] Preferably, x, n, and y satisfy the following requirements: 0.3 < x ≤ 0.5, 0.02 < n ≤ 0.04, 0 < y ≤ 0.03.
[0006] The raw materials for preparing the ceramic include powders, and the powders include: CaCO3, Pb3O4, Re2O3, ZrO2, SnO2, where Re includes any two of La, Sm, Nd, Eu, Gd, Pr, Dy, and Yb.
[0007] The raw materials for preparing the ceramic further include: solvents, plasticizers, dispersants, binders, and homogenizers.
[0008] Preferably, by weight percentage, the raw materials for preparing the ceramic include: 30 - 60% solvents, 0.5 - 7% plasticizers, 0.5 - 5% dispersants, 5 - 10% binders, 1 - 4% homogenizers, and the powders make up the balance.
[0009] Preferably, the solvent includes at least one of toluene, ethyl acetate, ethanol, and methyl ethyl ketone.
[0010] More preferably, the solvent includes toluene and ethanol, and the mass ratio of toluene to ethanol is (1 - 5):1.
[0011] Preferably, the plasticizer includes at least one of polyethylene glycol, dibutyl phthalate, triethyl citrate, dibutyl sebacate, diethyl sebacate, dibutyl phthalate, and acetyltriethyl citrate.
[0012] More preferably, the plasticizer includes polyethylene glycol and dibutyl phthalate, and the mass ratio of polyethylene glycol to dibutyl phthalate is (0.5 - 1.5):1.
[0013] Preferably, the dispersant includes at least one of tributyl phosphate, ethoxylate, castor oil, fish oil, phosphate ester, and triethanolamine.
[0014] Preferably, the binder includes at least one of polyvinyl butyral, polyvinyl alcohol, polymethyl methacrylate, polyethyl methacrylate, methyl cellulose, and ethyl cellulose.
[0015] Preferably, the homogenizer includes cyclohexanone or cyclohexane.
[0016] The second aspect of the present invention provides a method for preparing an A-site double rare earth ion co-doped antiferroelectric ceramic, comprising the following steps:
[0017] S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic;
[0018] S2, ball-milling the powder to mix evenly, drying, grinding, pre-sintering, and ball-milling again to obtain basic ceramic powder;
[0019] S3, uniformly mixing the basic ceramic powder with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a slurry, and obtaining a ceramic green body by tape casting;
[0020] S4, sintering the ceramic green body to obtain.
[0021] The pre-sintering treatment adopts a multi-step pre-sintering method, the pre-sintering temperature is 750-950°C, the heating rate is 1-8°C / min, the cooling rate is 1-10°C / min, and the holding time is 2-5 h.
[0022] Preferably,
[0023] The sintering in step S4 adopts an extrusion stacking integrated sintering method: ceramic debinding is performed first, and then sintering is performed.
[0024] In step S4, the ceramic debinding temperature is 500-600°C, the heating rate is 0.5-5°C / min, and the temperature is kept for 5-8 hours.
[0025] The sintering temperature in step S4 is 1100-1250°C, the heating rate is 1-8°C / min, the cooling rate is 1-10°C / min, and the heat preservation time is 2-4 hours.
[0026] Preferably, the thickness of the ceramic is 20-50 μm.
[0027] More preferably, the ceramic has a thickness of 23-40 μm.
[0028] Preferably, the breakdown electric field of the ceramic is 800-1240 kV / cm, the forward turning electric field is 620-720 kV / cm, and the reverse electric field is 520-620 kV / cm.
[0029] The applicant has found that the general formula of ceramic structure is: Pb (1.01-1.5n-y) M n Ca y (Zr 1-x Sn x ) 0.995O3; where M includes rare earth elements, and 0 < x ≤ 0.5, 0 < n ≤ 0.05, 0 < y ≤ 0.05; constructing ceramics with multi-element A-site substitution not only improves the stability of the antiferroelectric phase of the ceramics, that is, the antiferroelectric-ferroelectric phase transition electric field shifts towards a higher electric field direction, but also promotes densification growth and improves the breakdown electric field of the antiferroelectric ceramics. The Pb(Zr,Sn)O3 structure is a perovskite structure, and Pb 2+ is located at the corners of the oxygen octahedron, and O 2- exists at the face-centered position of the oxygen octahedron, Zr 4+ and Sn 4+ exist at the center of the oxygen octahedron. This structure is conducive to regulating the material properties through ion substitution. By regulating rare earth ions and combining multiple ball milling and multi-step pre-sintering methods, powders with smaller grain sizes are obtained. The obtained powders are added with solvents, plasticizers, dispersants, binders, and homogenizers and uniformly mixed to form a tape-casting slurry. A ceramic green body is obtained through tape-casting, and a ceramic with good density is sintered by an integrated extrusion and burying sintering method. Due to the co-doping of double rare earth ions at the A-site and supplemented by an advanced sintering method, grain refinement can be achieved, making the ceramic material more dense, enhancing its breakdown electric field, and further enhancing the energy storage performance.
[0030] The third aspect of the present invention provides an application of an antiferroelectric ceramic co-doped with double rare earth ions at the A-site, which is applied to a dielectric energy storage capacitor, and an electrode is prepared on the dielectric energy storage material by using an ion sputtering instrument.
[0031] Beneficial effects
[0032] 1. The general formula of the ceramic structure in this application is: Pb (1.01-1.5n-y) M n Ca y (Zr 1-x Sn x ) 0.995 O3; where M includes rare earth elements, and 0 < x ≤ 0.5, 0 < n ≤ 0.05, 0 < y ≤ 0.05, which not only improves the stability of the antiferroelectric phase of the ceramics, but also promotes densification growth and improves the breakdown electric field of the antiferroelectric ceramics.
[0033] 2. The powders prepared by this application using ball milling and multi-step pre-sintering methods have smaller particle sizes, can improve the density of the tape-casting film, and can also inhibit the growth size of ceramic grains, further improving the breakdown electric field of the ceramics.
[0034] 3. This application uses a specific tape-casting process, making the thickness of the prepared antiferroelectric ceramic 25 - 40 μm, the energy storage density 23 - 35 J / cm 3 , and the energy storage efficiency up to more than 70%.
[0035] 4. In the ferroelectric ceramic material, in addition to Pb at the A-site 2+In addition, by selecting several elements from the components consisting of Ca, La, Sm, Nd, Eu, Gd, Pr, Dy and Yb to construct antiferroelectric ceramics, the field-induced antiferroelectric-ferroelectric phase transition electric field can be enhanced and hysteresis losses can be reduced.
[0036] 5. Compared with the prior art, the energy storage density of the ceramic material prepared in this application is increased by 6~25 J / cm 3 , the discharge time is significantly shortened, and the energy storage density and efficiency are comparable to the performance of multilayer ceramic capacitors currently reported.
[0037] 6. The A-site double rare earth ion co-doped antiferroelectric ceramics prepared in this application can be used for energy storage capacitors and have good application prospects in pulse power systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The XRD curves of the ceramics of the embodiments and comparative examples are shown in FIG.
[0039] Figure 2 The SEM curves of the ceramics of the embodiments and comparative examples are shown in FIG.
[0040] Figure 3 This is the hysteresis loop of the ceramic of Example 1 under the breakdown electric field.
[0041] Figure 4 This is the hysteresis loop of the ceramic of Example 2 under the breakdown electric field.
[0042] Figure 5 This is the hysteresis loop of the ceramic of Example 3 under the breakdown electric field.
[0043] Figure 6 This is the hysteresis loop of the ceramic of Comparative Example 1 under the breakdown electric field.
[0044] Figure 7 This is the hysteresis loop of the ceramic of Comparative Example 2 under the breakdown electric field.
[0045] Figure 8 The forward turning electric field and reverse turning electric field data of the ceramics of the embodiments and comparative examples are shown in FIG.
[0046] Fig. 9 The ceramic energy storage density and energy storage efficiency of the embodiments and comparative examples are shown. DETAILED DESCRIPTION
[0047] Example 1
[0048] A double rare earth ion co-doped antiferroelectric ceramic at the A site, the general structure of the ceramic is: Pb 0.92 La 0.02 Ca 0.03 Nd 0.02 (Zr 0.6 Sn0.4 ) 0.995 O3.
[0049] Calculated by weight percentage, the raw materials for preparing the ceramic are: 40% solvent (toluene: ethanol weight ratio is 3:1), 4% plasticizer (polyethylene glycol: dibutyl phthalate weight ratio is 1:1), 2.5% dispersant (tributyl phosphate), 7% binder (polyvinyl butyral), 2.4% homogenizer (cyclohexanone), and the balance is made up of powder.
[0050] The powders are: CaCO3, Pb3O4, ZrO2, SnO2, La2O3 and Nd2O3.
[0051] The molar ratio of CaCO3, Pb3O4, ZrO2, SnO2, La2O3 and Nd2O3 is 0.03:0.307:0.597:0.398:0.01:0.01.
[0052] A method for preparing an A-site double rare earth ion co-doped antiferroelectric ceramic comprises the following steps:
[0053] S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic;
[0054] S2, the powder is mixed by wet high-energy ball milling, according to the mass ratio of powder: ball: ethanol 1:1.5:1.2, the mixing time is 12 h, and the components are fully mixed; after drying and grinding, it is passed through a 60-mesh sieve, placed in a crucible and compacted, and then a multi-step pre-sintering method is used, the specific method is to first heat it to 950 ℃, the heating rate is 3 ℃ / min, then cool it to 900 ℃ within 10 min, and then cool it to 850 ℃ within 5 min, and keep it warm for 3 h to obtain the basic ceramic powder;
[0055] S3, grinding the base ceramic powder, passing it through a 200-mesh screen, and uniformly mixing it with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a casting slurry, casting the obtained casting slurry, cutting the large film obtained by casting with a slicer, cutting the large film into small pieces of 15*15 mm, and then vacuum sealing the small pieces, performing cold isostatic pressing at 200 MPa, and maintaining the pressure for 15 min to form a ceramic green body;
[0056] S4, sintering the ceramic green body: placing it at a temperature of 550°C for 6 hours for debinding treatment, and then keeping it at a sintering temperature of 1150°C for 3 hours to obtain the green body.
[0057] Example 2
[0058] A double rare earth ion co-doped antiferroelectric ceramic at the A site, the general structure of the ceramic is: Pb 0.895 La 0.02Ca 0.04 Sm 0.03 (Zr 0.6 Sn 0.4 ) 0.995 O3.
[0059] Calculated by weight percentage, the raw materials for preparing the ceramic are: 40% solvent (toluene: ethanol weight ratio is 3:1), 4% plasticizer (polyethylene glycol: dibutyl phthalate weight ratio is 1:1), 2.5% dispersant (tributyl phosphate), 7% binder (polyvinyl butyral), 2.4% homogenizer (cyclohexanone), and the balance is made up of powder.
[0060] The powders are: CaCO3, Pb3O4, ZrO2, SnO2, La2O3 and Sm2O3.
[0061] The molar ratio of CaCO3, Pb3O4, ZrO2, SnO2, La2O3 and Sm2O3 is 0.04:0.298:0.597:0.398:0.01:0.015.
[0062] A method for preparing an A-site double rare earth ion co-doped antiferroelectric ceramic comprises the following steps:
[0063] S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic;
[0064] S2, the powder is mixed by wet high-energy ball milling, according to the mass ratio of powder: ball: ethanol 1:1.5:1.2, the mixing time is 12 h, and the components are fully mixed; after drying and grinding, it is passed through a 60-mesh sieve, placed in a crucible and compacted, and then a multi-step pre-sintering method is used, the specific method is to first heat it to 950 ℃, the heating rate is 3 ℃ / min, then cool it to 900 ℃ within 10 min, and then cool it to 850 ℃ within 5 min, and keep it warm for 3 h to obtain the basic ceramic powder;
[0065] S3, grinding the base ceramic powder, passing it through a 200-mesh screen, and uniformly mixing it with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a casting slurry, casting the obtained casting slurry, cutting the large film obtained by casting with a slicer, cutting the large film into small pieces of 15*15 mm, and then vacuum sealing the small pieces, performing cold isostatic pressing at 200 MPa, and maintaining the pressure for 15 min to form a ceramic green body;
[0066] S4, sintering the ceramic green body: placing it at a temperature of 550°C for 6 hours for debinding treatment, and then keeping it at a sintering temperature of 1150°C for 3 hours to obtain the green body.
[0067] Example 3
[0068] A double rare earth ion co-doped antiferroelectric ceramic at the A site, the general structure of the ceramic is: Pb 0.92 La 0.02 Yb 0.04 (Zr 0.5 Sn 0.5 ) 0.995 O3.
[0069] Calculated by weight percentage, the raw materials for preparing the ceramic are: 40% solvent (toluene: ethanol weight ratio is 3:1), 4% plasticizer (polyethylene glycol: dibutyl phthalate weight ratio is 1:1), 2.5% dispersant (tributyl phosphate), 7% binder (polyvinyl butyral), 2.4% homogenizer (cyclohexanone), and the balance is made up of powder.
[0070] The powders are: Pb3O4, ZrO2, SnO2, La2O3 and Yb2O3.
[0071] The molar ratio of Pb3O4, ZrO2, SnO2, La2O3 and Yb2O3 is 0.307:0.4975:0.4975:0.01:0.02.
[0072] A method for preparing an A-site double rare earth ion co-doped antiferroelectric ceramic comprises the following steps:
[0073] S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic;
[0074] S2, the powder is mixed by wet high-energy ball milling, according to the mass ratio of powder: ball: ethanol 1:1.5:1.2, the mixing time is 12 h, and the components are fully mixed; after drying and grinding, it is passed through a 60-mesh sieve, placed in a crucible and compacted, and then a multi-step pre-sintering method is used, the specific method is to first heat it to 950 ℃, the heating rate is 3 ℃ / min, then cool it to 900 ℃ within 10 min, and then cool it to 850 ℃ within 5 min, and keep it warm for 3 h to obtain the basic ceramic powder;
[0075] S3, grinding the base ceramic powder, passing it through a 200-mesh screen, and uniformly mixing it with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a casting slurry, casting the obtained casting slurry, cutting the large film obtained by casting with a slicer, cutting the large film into small pieces of 15*15 mm, and then vacuum sealing the small pieces, performing cold isostatic pressing at 200 MPa, and maintaining the pressure for 15 min to form a ceramic green body;
[0076] S4, sintering the ceramic green body: placing it at a temperature of 550°C for 6 hours for debinding treatment, and then keeping it at a sintering temperature of 1150°C for 3 hours to obtain the green body.
[0077] Comparative Example 1
[0078] An antiferroelectric ceramic, the general structure of which is: Pb 1.01 (Zr 0.6 Sn 0.4 ) 0.995 O3.
[0079] Calculated by weight percentage, the raw materials for preparing the ceramic are: 40% solvent (toluene: ethanol weight ratio is 3:1), 4% plasticizer (polyethylene glycol: dibutyl phthalate weight ratio is 1:1), 2.5% dispersant (tributyl phosphate), 7% binder (polyvinyl butyral), 2.4% homogenizer (cyclohexanone), and the balance is made up of powder.
[0080] The powders are: Pb3O4, ZrO2 and SnO2.
[0081] The molar ratio of Pb3O4, ZrO2 and SnO2 is 0.337:0.597:0.398.
[0082] A method for preparing an antiferroelectric ceramic comprises the following steps:
[0083] S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic;
[0084] S2, the powder is mixed by wet high-energy ball milling, according to the mass ratio of powder: ball: ethanol 1:1.5:1.2, the mixing time is 12 h, and the components are fully mixed; after drying and grinding, it is passed through a 60-mesh sieve, placed in a crucible and compacted, and then a multi-step pre-sintering method is used, the specific method is to first heat it to 950 ℃, the heating rate is 3 ℃ / min, then cool it to 900 ℃ within 10 min, and then cool it to 850 ℃ within 5 min, and keep it warm for 3 h to obtain the basic ceramic powder;
[0085] S3, grinding the base ceramic powder, passing it through a 200-mesh screen, and uniformly mixing it with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a casting slurry, casting the obtained casting slurry, cutting the large film obtained by casting with a slicer, cutting the large film into small pieces of 15*15 mm, and then vacuum sealing the small pieces, performing cold isostatic pressing at 200 MPa, and maintaining the pressure for 15 min to form a ceramic green body;
[0086] S4, sintering the ceramic green body: placing it at a temperature of 550°C for 6 hours for debinding treatment, and then keeping it at a sintering temperature of 1150°C for 3 hours to obtain the green body.
[0087] Comparative Example 2
[0088] An antiferroelectric ceramic, the general structure of which is: Pb 0.98 La0.02 (Zr 0.6 Sn 0.4 ) 0.995 O3.
[0089] Calculated by weight percentage, the raw materials for preparing the ceramic are: 40% solvent (toluene: ethanol weight ratio is 3:1), 4% plasticizer (polyethylene glycol: dibutyl phthalate weight ratio is 1:1), 2.5% dispersant (tributyl phosphate), 7% binder (polyvinyl butyral), 2.4% homogenizer (cyclohexanone), and the balance is made up of powder.
[0090] The powders are: Pb3O4, ZrO2, SnO2 and La2O3.
[0091] The molar ratio of Pb3O4, ZrO2, SnO2 and La2O3 is 0.327:0.597:0.398:0.01.
[0092] A method for preparing an antiferroelectric ceramic comprises the following steps:
[0093] S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic;
[0094] S2, the powder is mixed by wet high-energy ball milling, according to the mass ratio of powder: ball: ethanol 1:1.5:1.2, the mixing time is 12 h, and the components are fully mixed; after drying and grinding, it is passed through a 60-mesh sieve, placed in a crucible and compacted, and then a multi-step pre-sintering method is used, the specific method is to first heat it to 950 ℃, the heating rate is 3 ℃ / min, then cool it to 900 ℃ within 10 min, and then cool it to 850 ℃ within 5 min, and keep it warm for 3 h to obtain the basic ceramic powder;
[0095] S3, grinding the base ceramic powder, passing it through a 200-mesh screen, and uniformly mixing it with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a casting slurry, casting the obtained casting slurry, cutting the large film obtained by casting with a slicer, cutting the large film into small pieces of 15*15 mm, and then vacuum sealing the small pieces, performing cold isostatic pressing at 200 MPa, and maintaining the pressure for 15 min to form a ceramic green body;
[0096] S4, sintering the ceramic green body: placing it at a temperature of 550°C for 6 hours for debinding treatment, and then keeping it at a sintering temperature of 1150°C for 3 hours to obtain the green body.
[0097] Performance testing methods and data
[0098] The following performance tests were carried out in the embodiments and comparative examples, and the test data are listed in Table 1.
[0099] 1. Carry out XRD test, such as Figure 1 As shown, the synthesis of A-site double rare earth ion co-doped antiferroelectric ceramics was confirmed based on the diffraction peaks.
[0100] 2. Conduct SEM test, such as Figure 2 As shown, the surface morphology of the ceramic shows that the grains are highly dense and small in size, and the cross section shows that the thickness is at the micron level (37.5μm).
[0101] 3. Cover the upper and lower surfaces with Au electrodes to test their electrical properties (Radiant's ferroelectric integrated test system): Breakdown electric field ( Figure 3-7 ), forward turning electric field and reverse turning electric field ( Figure 8 ), energy storage density and energy storage efficiency ( Fig. 9 and Table 1).
[0102] Table 1
[0103] <![CDATA[Releaseable energy storage density (J / cm 3 ).]]> Energy storage efficiency (%) Comparative Example 1 10 63 Comparative Example 2 16 79 Example 1 35 70 Example 2 26 79 Example 3 22 92
Claims
1. An A-site double rare earth ion co-doped antiferroelectric ceramic, characterized in that: The general formula of the ceramic structure is: Pb (1.01-1.5n-y) M n Ca y (Zr 1-x Sn x ) 0.995 O3; where M includes rare earth elements, and 0.3 < x ≤ 0.5, 0.02 < n ≤ 0.04, 0 < y ≤ 0.03; the rare earth elements include any two of La, Sm, Nd, and Yb, and the energy storage density of the ceramic is 23~35 J / cm 3 , and the energy storage efficiency is 70~92%; The preparation method of the A-site double rare earth ion co-doped antiferroelectric ceramic comprises the following steps: S1, weighing the powder according to the stoichiometry of the elements in the structure of the ceramic; S2, ball-milling the powder to mix evenly, drying, grinding, pre-sintering, and ball-milling again to obtain basic ceramic powder; S3, uniformly mixing the basic ceramic powder with a solvent, a plasticizer, a dispersant, a binder, and a homogenizer to form a slurry, and obtaining a ceramic green body by tape casting; S4, sintering the ceramic green body to obtain; The pre-sintering treatment adopts a multi-step pre-sintering method, the pre-sintering temperature is 750-950°C, the heating rate is 1-8°C / min, the cooling rate is 1-10°C / min, and the holding time is 2-5 h.
2. The A-site double rare earth ion co-doped antiferroelectric ceramic according to claim 1, characterized in that: The raw materials for preparing the ceramic include powders, and the powders include: CaCO3, Pb3O4, Re2O3, ZrO2, SnO2, wherein Re includes any two of La, Sm, Nd and Yb.
3. The A-site double rare earth ion co-doped antiferroelectric ceramic according to claim 2, characterized in that: The raw materials for preparing the ceramic also include: solvent, plasticizer, dispersant, binder and homogenizer.
4. The A-site double rare earth ion co-doped antiferroelectric ceramic according to claim 3, characterized in that: The sintering in step S4 adopts an extrusion stacking integrated sintering method: ceramic debinding is performed first, and then sintering is performed.
5. The A-site double rare earth ion co-doped antiferroelectric ceramic according to claim 4, characterized in that: In step S4, the temperature of ceramic debinding is 500-600°C, the heating rate is 0.5-5°C / min, and the temperature is kept for 5-8 hours.
6. The A-site double rare earth ion co-doped antiferroelectric ceramic according to claim 4 or 5, characterized in that: The sintering temperature in step S4 is 1100-1250°C, the heating rate is 1-8°C / min, the cooling rate is 1-10°C / min, and the heat preservation time is 2-4 hours.
7. An application of the A-site double rare earth ion co-doped antiferroelectric ceramic according to claim 1 or 2, characterized in that: Applicable to dielectric energy storage capacitors.
Citation Information
Patent Citations
A dielectric energy storage antiferroelectric ceramic material and its preparation method
CN107459350B
Lead zirconate-based anti-ferroelectric multilayer capacitor and preparation method thereof
CN106915965A
High-energy-storage lead zirconate-based antiferroelectric multilayer ceramic capacitor and preparation method thereof
CN111574198A